DISKURSUS INDO–PASIFIK: HEGEMONI AMERIKA, PERSAINGAN STRATEGIS, HINGGA TRANSFORMASI GEOPOLITIK KAWASAN - Soni , Irawan (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
Based on Donald Trump's statement "You Say Asia Pacific, I Say" Indo Pacific" became a hint for the changing geopolitics of the world which marks a fundamental change to global politics. The discourse of Indo-Pacific demands a fundamental shift in how to understand the dynamics of international politics, formerly known as Asia-Pacific. The emphasis on hegemonic practices, strategic competition, to geopolitical transformation of the region is the main scope that is then created from the projection of the US grand strategy. The Indo-Pacific is essentially an expansion of geographical coverage by involving India as a symbol of the dominant force in the Indian Ocean into a progressive US move to present structural obstacles to the dominance of Chinese military power.